2014
DOI: 10.1371/journal.pone.0115558
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Expression is Increased in Colon Adenoma and Carcinoma and Correlates with OGG1

Abstract: The ethiology of colon cancer is largely dependent on inflammation driven oxidative stress. The analysis of 8-oxodeoxyguanosine (8-oxodGuo) level in leukocyte DNA of healthy controls (138 individuals), patients with benign adenomas (AD, 137 individuals) and with malignant carcinomas (CRC, 169 individuals) revealed a significant increase in the level of 8-oxodGuo in leukocyte DNA of AD and CRC patients in comparison to controls. The counteracting mechanism is base excision repair, in which OGG1 and PARP-1 play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 48 publications
3
27
0
1
Order By: Relevance
“…Additionally, these observations align with studies demonstrating that PARP‐1 and PAR are elevated in PCa compared to benign prostatic hyperplasia in a Chinese cohort (Wu et al , ) and that PARP‐1 protein is elevated in cases of primary PCa as compared to normal controls (Salemi et al , ). In other tumor types, elevated PARP‐1 mRNA is associated with poor prognosis in gliomas (Li et al , ), PARP‐1 mRNA is elevated in colon carcinoma when compared to adenoma (Dziaman et al , ), PARP‐1 gene expression is associated with lymph node spread of malignant pleural mesothelioma (Walter et al , ), and PARP‐1 mRNA and protein are elevated in endometrial adenocarcinoma (Bi et al , ). Both PARP‐1 mRNA and protein are highly expressed in small cell lung cancer (Byers et al , ), but PARP‐1 protein has been shown to associate with longer PFS in limited‐stage small cell lung cancer (Kim et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these observations align with studies demonstrating that PARP‐1 and PAR are elevated in PCa compared to benign prostatic hyperplasia in a Chinese cohort (Wu et al , ) and that PARP‐1 protein is elevated in cases of primary PCa as compared to normal controls (Salemi et al , ). In other tumor types, elevated PARP‐1 mRNA is associated with poor prognosis in gliomas (Li et al , ), PARP‐1 mRNA is elevated in colon carcinoma when compared to adenoma (Dziaman et al , ), PARP‐1 gene expression is associated with lymph node spread of malignant pleural mesothelioma (Walter et al , ), and PARP‐1 mRNA and protein are elevated in endometrial adenocarcinoma (Bi et al , ). Both PARP‐1 mRNA and protein are highly expressed in small cell lung cancer (Byers et al , ), but PARP‐1 protein has been shown to associate with longer PFS in limited‐stage small cell lung cancer (Kim et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…PARP1 played an important role in DNA damage repair, [15][16][17], which made PARP1 a valuable therapeutic target in the research of disease drug. Recently, it was found that PARP1 presented high expression in a series of cancers, which provided a high-value target for the study of tumor detection, stage and biological characteristics [18][19][20][21][22][23]. The overexpression of PARP1 results from much DNA damage in cancer cells with unstable genes, instead of the induction of the activated specific carcinogenic pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of IhC staining was performed as described in detail earlier (28,29). Remmele and Stegner (30) scoring system was used.…”
Section: Methodsmentioning
confidence: 99%